2019
DOI: 10.1002/pmrj.12158
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autonomic Function by Physical Exercise in Patients with Fibromyalgia Syndrome: A Systematic Review

Abstract: Objective To evaluate the effects of physical exercise on autonomic dysfunction in patients with fibromyalgia syndrome (FM). Literature Survey and Methodology A systematic review of experimental studies published until December 2017 that analyzed the effect of physical exercise on autonomic dysfunction in patients with FM was performed using the PubMed, Pedro, Scopus, ScienceDirect, and Web of Science databases. Synthesis A total of 1105 articles were identified, 12 of which were included in the final analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Mood reflects a complex pattern of behaviors, feelings, thoughts, and physical and emotional states; a mood consists of six factors: anger, confusion, mood depression, fatigue, vigor, and tension (7)(8)(9)(10). To improve the physical and psychological symptoms and consequently the general health of patients with FM, physical exercise has been recommended as an alternative treatment in recent years (11)(12)(13)(14)(15). Among various types of physical exercise, strength training (ST) has been shown to be an effective treatment option in helping to reduce the most common symptoms of the syndrome (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Mood reflects a complex pattern of behaviors, feelings, thoughts, and physical and emotional states; a mood consists of six factors: anger, confusion, mood depression, fatigue, vigor, and tension (7)(8)(9)(10). To improve the physical and psychological symptoms and consequently the general health of patients with FM, physical exercise has been recommended as an alternative treatment in recent years (11)(12)(13)(14)(15). Among various types of physical exercise, strength training (ST) has been shown to be an effective treatment option in helping to reduce the most common symptoms of the syndrome (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…It is well established that aerobic exercise improves cardiorespiratory function in patients with FMS 19,109. In addition, an aquatic environment can allow higher-intensity exercises to be undertaken, with lower cardiovascular stress than is possible on land 19,110.…”
Section: Water Therapy Physiological Effects and Its Relationship Witmentioning
confidence: 99%
“…Endurance training is recommended by different medical societies for FM management (8,(11)(12)(13)(14) in the range of two to three sessions a week, allowing to respect a rest period and avoid exacerbation of symptoms, at least for a period of 4-6 weeks in order to see a decrease in symptoms (15,16) and a change in autonomic function (17). A light-intensity aerobic practice (15,18) does not allow a decrease in symptom intensity, rather indicating a moderate to vigorous intensity physical activity (MVPA) practice.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in pain was also measured in a resistance program followed for 8 weeks with three sessions a week (30). Recently, Andrade et al (17) identified a correlation between resistance training and reduction in psychological symptoms such as anxiety and depression. Muscle stretching and relaxation exercises also showed an impact on pain (31), pain perception and tolerance (32), quality of life, depression, and anxiety (33) Despite the absence of accurate recommendations on training modalities, as defined by the ACSM, a personalized and mixed training seems to be the best practice according to the EULAR recommendations (8), and it is also this type of training that is recommended for people suffering from chronic pain (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation